Facile synthesis of bismuth oxyhalogen-based Z-scheme photocatalyst for visible-light-driven pollutant removal: Kinetics, degradation pathways and mechanism. (10th July 2019) - Li, Bisheng; Lai, Cui; Xu, Piao; Zeng, Guangming; Huang, Danlian; Qin, Lei; Yi, Huan; Cheng, Min; Wang, Longlu; Huang, Fanglong; Liu, Shiyu; Zhang, Mingming
Abstract: Water pollution caused by heavy metal and organic pollutant becomes a rigorous problem, thereby a clean and sustainable technology should be developed to resolve this situation. In this work, a novel AgI/Bi24 O31 Cl10 Z-scheme photocatalysis system was designed to overcome this problem. The prepared AgI/Bi24 O31 Cl10 composite was characterized by many means such as X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and Brunauer-Emmett-Teller (BET). The designed Z-scheme photocatalysis system conquers difficulties of traditional photocatalysts of the fast photogenerated charge carrier recombination and weak redox ability, thereby held remarkable catalytic activity for Cr (VI) reduction and tetracycline (TC) oxidation, approximately 85.36% and 78.26% of tetracycline and Cr (VI) can be removed under visible light illumination for 1 h. Some factors like contaminant concentrations, inorganic cation, inorganic anion, and water resources on catalytic activity were explored and the influence mechanism was discoursed. Importantly, the cyclic experiment suggested that the removal efficiency did not have obvious loss after five consecutive experiments, confirming its stability and reusability. The photodegradation pathway of TC was also proposed according to liquid chromatography-mass/mass spectrometry (LC-MS) and three dimensional excitation-emission matrix fluorescence spectra (3D EEMs). Furthermore, this Z-scheme photocatalysis mechanism for Cr (VI) reduction and TC oxidation was proposed based on trapping experiment and electron spin resonance (ESR) measurement. This study sheds lights on the design of Z-scheme photocatalysis system with sunlight as driving force for refractory organic pollutants removal. Graphical abstract: Image 1 Highlights: The novel Z-scheme AgI/Bi24 O31 Cl10 heterojunction photocatalyst has been first prepared. AgI/Bi24 O31 Cl10 showed superior catalytic activity for Cr (Ⅵ) reduction and tetracycline oxidation. The interfacial redox reaction was promoted. The photogenerated charge carrier separation efficiency was enhanced. The photodegradation pathway and photocatalytic mechanism was proposed.